Effect of combined prebiotics from different sources and microorganism mix on growth performance of milkfish, Chanos chanos forsskal, 1775 - Siti Aslamyah; Zainuddin; Mohammed, Ayman Alameen (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study was conducted to determine the effect of using synbiotics in artificial feed on growth, digestive enzyme activities, glycogen levels, hepatosomatic index, body chemical composition, nutrient retention, gastric emptying rate, and blood glucose levels of milkfish. Milkfish (4.78 ± 0.16 g) were stocked at density of 20 fish per aquarium (50 × 40 × 35 cm3) containing 48 L of water with a salinity of 20 ppt and equipped with a recirculation system. Fish were fed three times a day (7:00 AM, 12:00, and 17:00 PM) at a feeding rate of 5% for 50 days. This study used a completely randomized design (CRD) with five treatments and three replicates. Synbiotics consisting of 10 mL/kg microorganism mix and 2% different sources of prebiotics (sweet potatoes, Kappaphycus alvarezii, green beans, and red onion) were added to the artificial feed. The results indicated that milkfish-fed sweet potatoes and green beans experienced significant growth improvement and enhanced feed efficiency. These prebiotic sources also positively impacted digestive enzyme activities, potentially improving nutrient utilization. Additionally, green beans exhibited the most pronounced effects on liver and muscle glycogen levels, hepatosomatic index, and energy content. Body composition data showed alterations in protein, fat, ash, crude fiber, and nitrogen-free extract percentages due to prebiotic sources. Green beans demonstrated the highest nutrient retention rates. Moreover, the rate of gastric emptying and blood glucose that was observed reached its peak, and the fastest peak decreased in the prebiotic treatment, which was sourced from green beans and sweet potatoes.